Malting and brewing process optimization of elite lines of triticale for beer production - Nocente, Francesca; Francesco, Giovanni; Marconi, Ombretta; Floridi, Simona; Latini, Arianna; Cantale, Cristina; Galeffi, Patrizia; Ammar, Karim; Gazza, Laura (Springer, 2025)
Triticale stands out as a valuable food ingredient due to its nutritional and functional attributes derived from both wheat and rye. The growing demand for agrifood diversity has resulted in increased interest in triticale for food and beverage production, and as research and development of new breeding lines continue, triticale is likely to play a more prominent role in the food industry, contributing to healthy, diversified, and sustainable food systems. In this context, triticale is suitable for beer production, which is traditionally made from barley malt, but can be produced by the addition of alternative grains. In this study, five triticale lines were tested both as unmalted, to produce an auto-saccharified wort, and as malted grain. Upon the malting process, line 7 was found to be the most effective in terms of malting performance; three beer formulations with different percentages of addition (i.e., 40, 70, and 100%) of malted selected triticale lines were produced in an experimental pilot plant and characterized for percentage of alcohol, foam stability, haze, and visual and taste profile. The beer containing 40% malted triticale was judged to be particularly interesting in terms of its stable foam, lighter color, greater attenuation, and lower turbidity than those produced from 70% or 100% malted triticale. This formulation could have potential for scale-up in industrial production and for the market.